Temperature-induced phase averaging in one-dimensional mesoscopic systems - Jakobs, Severin Georg; Enss, Tilman (Physical review. B, Condensed matter and materials physics, 2007)
We analyze phase averaging in one-dimensional interacting mesoscopic systems with several barriers and show that for incommensurate positions an independent average over several phases can be induced by finite temperature. For three strong barriers with conductances Gi and mutual distances larger than the thermal length, we obtain G∼√G1G2G3 for the total conductance G. For an interacting wire, this implies power laws in G(T) with novel exponents, which we propose as an experimental fingerprint to distinguish temperature-induced phase averaging from dephasing.
Gesehen am 24.11.2017